Cognitive Behavioral Therapy for Chronic Pain - Afrina, Riska; Karimah, Azimatul (Biomolecular and Health Science Journal, 2019)
Introduction: Pain is a complex stressor that has a major influence on several aspects of a person's physical, psychological, work and financial functions, especially in the form of chronic pain. The approach to chronic pain medically can sometimes not solve the problem as a whole, so that in its management psychological approaches such as cognitive and behavioral therapy (CBT) are needed.Methods: We searched PubMed, Science Direct, and Google Scholar for search articles in English terms "chronic pain", "cognitive behavioral therapy", "pain management", and "efficacy". Searching using the keywords above showed 40 articles, but which were taken were 8 articles from the last 5 years.Results: The method of intervention was carried out with a cognitive-behavioral approach in the form of traditional CBT, telephone-based CBT, coping skills training, cognitive-behavioral based physical therapy or CBT-based self-management. The research parameters used to measure the success rate of the interventions were pain intensity, physical function, psychological pressure, disability, fatigue, quality of life, coping strategies, catastrophization, and depression. The duration of the study varied from 5 weeks to 10 weeks, with a variation of 20-60 minutes per therapy session, except in studies using group therapy can take up to 5-7 hours per day. Some studies also conducted evaluation at the third and six months after treatment. The aim of the CBT approach was to independently improve self-efficacy in pain management.Conclusion: Cognitive behavioral approaches combined with other therapeutic modalities can improve the physical function of patients with chronic pain.